Missed HIV care appointments and high body mass index predict hypertension risks at diagnosis: a risk identifying opportunity among people living with HIV for global health - Ngugi, Silvia; Mutie, Cyrus; Wanjiku, Victoria; Chweya, Reagan; Gachohi, John; Ngure, Kenneth (International Journal Of Community Medicine And Public Health, 2024)
Background: Chronic conditions, including diabetes and hypertension among people living with HIV/AIDS (PLWHIV), require long-term adherence to treatment and regular follow-ups for symptom checkups and management to prolong life and improve its quality. To inform the design of patient-centered HIV-NCD interventions, this study determined predictors of hypertension and diabetes (non-communicable diseases-NCD) among PLWHIV. Methods: This study adopted a cross-sectional study design. Attendance registers of PLWHIV attending the comprehensive care clinic at Murang'a referral hospital served as a sampling frame. The first study participant was randomly selected using a lottery method, while other participants were systematically sampled and enrolled. PLWHIV were clinically examined for NCD (hypertension and/or diabetes) screening and body mass index (BMI). Logistic regression models predicted associations with risk factors linked to the selected NCD among PLWHIV. Results: A total of 281 PLWHIV were recruited, of these 192 (68%) were female, while 91% were aged above 35 years. We identified 77 (27%) PLWHIV with hypertension, and none had diabetes. About 70% of the PLWHIV with NCD missed HIV care appointments. About 89% of the PLWHIV were obese and overweight. Higher BMI (Odds ratio (OR)=1.15 95%CI 1.06, 1.24) and missing HIV care appointments (OR=2.12 95%, CI 1.23, 3.95) increased the risk of hypertension among PLWHIV. Conclusions: We establish increased risks to NCD associated with higher BMI and missed scheduled HIV-linked care among PLWHIV. To improve global health, identifying and understanding determinants of missed HIV care appointments will help to re-engage defaulters while promoting regular screening for NCD profiles.